ISLAMIC POLITICAL AWARENESS OF GENERATION Z IN THE ERA OF DIGITAL DEMOCRACY - Dhea Amelia Nanda Lubis; Zulkarnain (SOSIOEDUKASI, 2026)
This study aims to analyze the Islamic political awareness of Generation Z students specifically those from the Faculty of Ushuluddin and Islamic Studies at UIN North Sumatra in the era of digital democracy. Employing a descriptive qualitative approach with purposive sampling, the study selected informants based on specific criteria, active Generation Z status, experience accessing political information via digital media, and prior involvement in campus political discussions or activities. Data were collected through in-depth interviews, limited participant observation, and documentation of digital activities, then analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The results indicate that the students' Islamic political awareness tends to be normative and symbolic rather than fully developed at a critically reflective level. While social media platforms such as TikTok, Instagram, YouTube, and X serve as primary sources for shaping political perceptions, limited digital political literacy renders students vulnerable to the simplification of discourse and polarization. Political participation manifests predominantly through digital expressions such as likes, shares, and comments rather than through substantive deliberative engagement in academic forums. These findings highlight a gap between the ideals of Islamic political values and the practice of digital democracy among Generation Z; consequently, there is a need to strengthen critical and integrative Islamic political literacy within Islamic higher education.